Sosialisasi pencegahan stunting dengan memanfaatkan tanaman remunggai guna menyiapkan sumber daya manusia unggul di Kelurahan Panorama Kota Bengkulu - Puspita, Veny; Safrianti, Sintia; Waliamin, Janusi (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2022)
Superior human resources are a mandatory requirement to make Indonesia advanced, but in preparing superior human resources there is still a challenge, namely stunting. Basically, there are two types of nutrients that children need to grow and avoid stunting, namely macronutrients (macronutrients) and micronutrients (micronutrients). The purpose of this activity is to foster public understanding in the Panorama Village, Bengkulu City, to create creative and innovative food preparations that are rich in nutrients so that they will create superior human resources. After this community service activity was carried out there was an increase in the knowledge of posyandu participants by more than 70%. The increase in the knowledge of the participants was due to the fact that the material that had been delivered was easy for the participants to understand. The participants were also taught directly how to use the remunggai plant to make nutritious food for children. So that stunting can be prevented and in the future will produce superior and productive human resources. This activity also resulted in a joint commitment from all stakeholders, including PKK mobilizing team members, posyandu cadres, puskesmas staff and posyandu members to support Stunting Prevention by Utilizing Remunggai Plants to Prepare Superior Human Resources in the Panorama sub-district, Bengkulu City.